Causal temporal renormalisation group flow of the energy-momentum tensor - Heller, Markus; Pawlowski, Jan M. (Arxiv, 2021)
We derive the temporal renormalisation group flow of the energy-momentum tensor at the example of a general scalar theory. The local causal structure of the temporal renormalisation group flow allows to monitor and control causality, unitarity and general conservation laws at each infinitesimal renormalisation group step. We explore energy-conserving truncations in a comparison of generic flows and the causal temporal flow of the energy-momentum tensor. We also observe that the temporal regulator preserves scale invariance, which is violated for generic momentum regulators. Specifically we discuss the relation of these terms to the trace anomaly of the energy-momentum tensor. Moreover, we show that the causal temporal flow of the energy-momentum tensor can be integrated analytically, and demonstrate, that the result is consistent with energy conservation.